Valoración del paisaje y ordenación del territorio en los medios costeros de Galicia - Queijeiro J.M.G. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
A methodology for landscape assessment and evaluation that has been applied in certain coastal environments of Galicia standing out for its natural value is proposed. The capacity of landscape to synthesise a great number of characteristics of the environment, justify its election for these kind of works, contributing to facilitate information transfer between specialists in the study of natural resources and technicians coming from urbanism or administration fields. In this way, this methodology becomes an instrument that contributes to improve the management of environment, facilitating the taking of decisions for the spatial distribution of the different activities intended to be located in that parcel of territory.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)